Solving Intergenerational Communication Problems in Tourism and Hospitality Enterprises - Luka, Ineta; Drozdova, Valerija; Šakytė-Statnickė, Gita; Budrytė-Ausiejienė, Laurencija (Journal of Education Culture and Society, 2023)
Aim. The aim of the research is to identify intergenerational communication problems in tourism and hospitality enterprises and define teaching/learning initiatives and methodologies required to develop employees’ competencies to solve intergenerational communication problems.Methods. 12 semi-structured expert interviews with tourism and hospitality business owners and/or top-level management in three countries (Lithuania, Latvia, and Sweden) were conducted to collect information on generational differences in communication and intergenerational communication problems in the company. Qualitative content analysis was applied for data analysis.Results. Nine main groups of intergenerational communication problems have been detected and corresponding teaching/learning initiatives and methodologies that take into account the specific characteristics of each generation are recommended to eliminate each of the problems identified.Conclusion. Generational differences and differences in communication lead to intergenerational communication conflicts in tourism and hospitality enterprises. The suggestions on organising adult learners’ teaching/learning process based on generational differences may be applicable in workplace learning and also in educational institutions providing adult education.Cognitive value. The paper focusses on analysing intergenerational aspects in communication processes in tourism and hospitality enterprises and offers the means of solving communication conflicts by employing certain adult teaching/learning initiatives and methodologies suitable to non-formal and formal adult learning.